การบริหารงานวิชาการสำหรับการจัดการศึกษาทางไกลผ่านดาวเทียมของโรงเรียนขนาดเล็กในสามจังหวัดชายแดนภาคใต้ - หมั่นดี, นิดา; หฤทัยธนาสันติ์, ธีร; วาณิชย์ศุภวงศ์, ผ่องศรี; แวอุเซ็ง, นิเลาะ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 2 (2562): Academic Services Journal, Prince of Songkla University, 2019)
งานวิจัยเชิงคุณภาพนี้เป็นแบบ cased study ซึ่งศึกษาโรงเรียนขนาดเล็กที่มีแนวปฏิบัติที่ดี (good practice) ด้านการจัดการศึกษาทางไกลผ่านดาวเทียม โดยมีวัตถุประสงค์เพื่อศึกษาแนวทางการบริหารงานวิชาการสำหรับการจัดการศึกษาทางไกลผ่านดาวเทียมของโรงเรียนขนาดเล็กในสามจังหวัดชายแดนภาคใต้ ผู้ให้ข้อมูลสำคัญจำนวน 21 คน เป็นผู้อำนวยการโรงเรียน ครูวิชาการ และครูผู้สอน จากโรงเรียนขนาดเล็กในจังหวัดปัตตานี ยะลา และนราธิวาส ที่มีผลสัมฤทธิ์ทางการเรียนระดับชาติ (O-NET) สูงกว่าระดับประเทศ จำนวน 3 โรงเรียน เครื่องมือในการวิจัยเป็นแบบสัมภาษณ์กึ่งโครงสร้าง เก็บข้อมูลด้วยการสัมภาษณ์เชิงลึกร่วมกับการศึกษาเอกสาร วิเคราะห์ข้อมูลโดยใช้การวิเคราะห์เนื้อหา ผลการวิจัยพบว่า แนวทางการบริหารงานวิชาการสำหรับการจัดการศึกษาทางไกลผ่านดาวเทียมในสามจังหวัดชายแดนภาคใต้ ประกอบด้วย 1) การวางแผนงานวิชาการ 2) การจัดการเรียนการสอน 3) การวัดประเมินผลการเรียนการสอน และ 4) การนิเทศติดตามและประเมินผล คำสำคัญ: การบริหารงานวิชาการ, การจัดการศึกษาทางไกลผ่านดาวเทียม, โรงเรียนขนาดเล็ก, จังหวัดชายแดนภาคใต้   This qualitative research is a cased study of small-sized schools with good practice in the educational management of distance learning television (DLTV).This research aimed to study guidelines of academic administration for educational management of distance learning television of small-sized school in the three southern border provinces. The purposeful selection were 21 key informants included administrators, academic teachers and teachers from 3 small-sized schools that had ordinary national education test (O-NET) higher than the national level in Pattani, Yala and Narathiwat. Research instruments were a semi-structured interview protocol, including in-depth interview related with documents study. Data were analyzed by using content analysis. The finding found that guidelines of academic administration for educational management of distance learning television of small-sized school in the three southern border provinces were 1) academic planning 2) teaching and learning 3) measurement of learning outcomes and 4) supervision, monitoring and evaluation. Keywords: academic administration, distance learning television, small-sized schools, southern border provinces